Challenges of Implementing the Kyushoku Program in Contemporary Japan: An Analysis of Policy, Media, and Social Reality - Althaf Gauhar Auliawan; Ichlasul Ayyub (KIRYOKU, 2026)
Kyushoku has long been recognized as a structured and successful school lunch program supporting nutrition education and child well-being in Japan. However, Kyushoku has recently faced various challenges amidst emerging global issues. This study aims to analyze the current implementation challenges of the Kyushoku program to provide developing countries with an understanding that this ideal program still requires improvement and targeted government intervention. This study uses a qualitative approach with a literature review method, through the analysis of credible data such as Japanese government policy documents, official survey reports, books, recent Japanese media reports, and relevant academic literature articles. The results reveal several key challenges in Kyushoku's implementation, such as food price inflation making it difficult for local governments to provide food that meets nutritional standards, inter-regional Inequality, food safety issues, and demographic decline in Japan. The study's findings suggest that the sustainability of the Kyushoku program depends on adaptive policy support, stable financial management, and stronger coordination among the government, schools, and related sectors. This study is expected to provide a critical perspective on the evolving reality of the Kyushoku program in modern Japanese society.